Methanol Electrooxidation on Pt-Ru Catalysts Dispersed in Conducting Polyaniline Films - Kessler, Teresita (2004)
Methanol electrooxidation was investigated on tailored Pt-Ru-polyaniline catalysts prepared applying dynamic potential routines. The electrodes characterized by SEM, EDX and TEM present a uniform distribution of metal particles about 100 nm in size, composed of Ru and Pt on the fibrous polymer matrix. The effect of concentration in the range 0.05-1 M and temperature in the range 20 to 60 °C on the methanol electrooxidation rate was determined. The apparent activation energy depends on the catalyst Ru content.